Hybrid decompression-based surgical strategy for treating multilevel thoracic ossification of the ligamentum flavum: a retrospective study - Cong Nie; Kaiwen Chen; Shenyan Gu; Feizhou Lyu; Jianyuan Jiang; Xinlei Xia; Chaojun Zheng (Asian Spine Journal)
Study Design A retrospective study design was adopted. Purpose This study investigated the surgical modification of laminectomy, including piecemeal and en bloc resections, and compared this hybrid approach with conventional en bloc laminectomy for treating multilevel thoracic ossification of the ligamentum flavum (TOLF). Overview of Literature En bloc laminectomy is the most commonly used method for managing symptomatic TOLF. However, this approach can easily cause intraoperative spinal cord irritation, dural tear, and cerebrospinal fluid leakage (CFL). Methods Motor-evoked potentials (MEPs) and somatosensory-evoked potentials (SEPs) were recorded in 48 patients with TOLF (hybrid 20 vs. en bloc 28) during surgery. Patients were categorized based on MEP/SEP improvement, deterioration, or no change, and MEP/SEP improvement rates were measured in the improvement group. Furthermore, all patients were assessed using the Ashworth and modified Japanese Orthopedic Association scores. Results The incidences of both MEP/SEP improvement (21.4% vs. 25.0%, p=0.772) and deterioration (21.4% vs. 20.0%, p=0.904) were similar between the en bloc and hybrid laminectomy groups, and no difference in preoperative and postoperative clinical assessments was observed between the two groups (p>0.05). In four patients (4/28, 14.3%) undergoing en bloc laminectomy, MEP amplitudes initially increased after OLF removal but gradually decreased. This delayed MEP reduction did not occur in the hybrid laminectomy group. Furthermore, more patients undergoing en bloc laminectomy had CFL than those undergoing hybrid laminectomy (46.4% vs. 15.0%, p=0.023). In the improvement group, the hybrid laminectomy group exhibited higher MEP improvement rates in the bilateral abductor hallucis than the en bloc laminectomy group (left side: 213.4%±35.9% vs. 152.5%±41.0%, p=0.028; right side: 201.2%±32.0% vs. 145.2%±46.3%, p=0.043). Conclusions Compared with en bloc laminectomy, hybrid laminectomy may be a safe and effective method for treating multilevel TOLF, potentially reducing intraoperative spinal cord irritation and CFL and causing relatively better functional recovery.